2018
DOI: 10.1002/jwmg.21490
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis: Informing recovery of Sierra Nevada bighorn sheep

Abstract: Survival in small populations (e.g., Sierra Nevada bighorn sheep or Sierra bighorn [Ovis canadensis sierrae]) is often highly variable. External selective pressures vary in the degree to which they regulate survival by sex and age class. Understanding the important factors and risks for different demographic classes helps managers design strategies that enhance the recovery of endangered species, including Sierra bighorn. Our goal was to determine what population‐level factors (e.g., climate, habitat, populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 82 publications
(138 reference statements)
2
51
0
Order By: Relevance
“…This pattern shows some latitudinal variation with forbs playing a more important role in more northern populations (Schroeder, Bowyer, Bleich, & Stephenson, ). Some Sierra bighorn populations are hypothesized to be limited by winter nutrition; recent work by Conner et al () was unable to find a signal of density dependent effects on adult survival, but suggested that these effects may be felt by younger, more vulnerable age classes. Distributions of mule deer Odocoileus hemionus overlapped with portions of some Sierra bighorn lower‐elevation winter ranges, but although both ungulates consume shrubs, they prefer different species, limiting the potential for direct competition (Johnson et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern shows some latitudinal variation with forbs playing a more important role in more northern populations (Schroeder, Bowyer, Bleich, & Stephenson, ). Some Sierra bighorn populations are hypothesized to be limited by winter nutrition; recent work by Conner et al () was unable to find a signal of density dependent effects on adult survival, but suggested that these effects may be felt by younger, more vulnerable age classes. Distributions of mule deer Odocoileus hemionus overlapped with portions of some Sierra bighorn lower‐elevation winter ranges, but although both ungulates consume shrubs, they prefer different species, limiting the potential for direct competition (Johnson et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Following extensive collection of data on causes of adult mortality, cougars accounted for more than half of known mortalities in our system (snow avalanches also played a major role; Conner et al, ; Johnson et al, ; Stephenson et al, ). Still, a wider suite of predators is present and may influence juvenile survival.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this method does not allow us to consider potential additive or lagged effects of the cumulative exposure to high‐risk habitats (Conner et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…We assumed that these habitat attributes could influence predation risk and the instantaneous risk of mortality (Whittington et al 2011). However, this method does not allow us to consider potential additive or lagged effects of the cumulative exposure to high-risk habitats (Conner et al 2018).…”
Section: Survival Analysesmentioning
confidence: 99%